2023
DOI: 10.1021/acs.jafc.2c07581
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Alleviated High-Fat-Diet-Induced Hepatic Pyroptosis by Mitophagy-ROS-CTSB-NLRP3 Pathway in Mice and AML12 Cells

Abstract: Apigenin is considered the most-known natural flavonoid and is abundant in a wide variety of fruits and vegetables. A high fat diet (HFD) can induce liver injury and hepatocyte death in multiple ways. Pyroptosis is an innovative type of programmed cell death. Moreover, excessive pyroptosis of hepatocytes leads to liver injury. We used HFD to induce liver cell pyroptosis in C57BL/6J mice in this work. After gavage of apigenin, apigenin can significantly reduce the level of lactate dehydrogenase (LDH) in liver t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In addition to energy and metabolism, mitochondria play a crucial role in regulating some key cellular processes, such as apoptosis and inflammation. A growing body of literature suggests that excessive ROS generated by defective mitochondria can result in the activation of NLRP3 inflammasome. , Recent studies have indicated the associations of PA-induced hepatocyte death with dysregulated inflammasome. NLRP3 inflammasome comprising multiple proteins could be activated by a wide variety of danger signals and provoke innate immune responses. , Assembly of the NLRP3 inflammasome activates caspase-1 via initiating cleavage of procaspase 1 into caspase-1, which subsequently converts the cytokine precursors pro-IL-1β into mature and biologically active IL-1β .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to energy and metabolism, mitochondria play a crucial role in regulating some key cellular processes, such as apoptosis and inflammation. A growing body of literature suggests that excessive ROS generated by defective mitochondria can result in the activation of NLRP3 inflammasome. , Recent studies have indicated the associations of PA-induced hepatocyte death with dysregulated inflammasome. NLRP3 inflammasome comprising multiple proteins could be activated by a wide variety of danger signals and provoke innate immune responses. , Assembly of the NLRP3 inflammasome activates caspase-1 via initiating cleavage of procaspase 1 into caspase-1, which subsequently converts the cytokine precursors pro-IL-1β into mature and biologically active IL-1β .…”
Section: Discussionmentioning
confidence: 99%
“…PINK1 acting as a molecular sensor detects signals of abnormal mitochondria for the recruitment and activation of Parkin. Through its E3 ubiquitin ligase activity, Parkin binds to the outer mitochondrial membrane, initiating multiple signaling events culminating in the engulfment of damaged mitochondria within lysosomes. , It has been shown that loss of PINK1 impairs mitophagy and that disabled mitophagy is one of the potential contributors to the onset of NAFLD. , In support of this, some studies reported inhibited PINK1/Parkin-mediated mitophagy in the livers of mice with NAFLD and PA-treated hepatocytes. , Conversely, restoring PINK1/Parkin-driven mitophagy rescued the mitochondrial dysfunction and preserved cellular integrity and homeostasis in hepatocytes. Here, our results connect the hepatoprotective effects of Hst to PINK1/Parkin-mediated mitophagy upregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies had uncovered important mitoprotective actions of apigenin in several disease models 37 . For example, apigenin was reported to reduce palmitic acid-induced mitochondrial dysfunction through mitophagy activation, resulting in decreased hepatic pyroptosis 38 . During LPS-caused neurotoxicity, apigenin was shown to activate mitochondrial fusion, an important mechanism safeguarding mitochondrial homeostasis, through a mechanism involving the Sirt3/PINK1/Parkin pathway 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on mice that were fed either a special diet or acid showed an increase in the level of reactive oxygen species. This led to the release of cathepsin B, which activated the NLRP3 inflammasome [154].…”
Section: Other Types Of Regulated Cell Deathmentioning
confidence: 99%